Grzeczność przy koreańskim stole – podstawowe zasady etykiety obowiązującej przy stole w Korei Południowej na przykładzie informacji dostępnych w sieci w języku polskim oraz wybranych scen z koreańskich seriali streamingowych - Barbara Maj-Malinowska (Linguistische Treffen in Wrocław, 2025)
In recent years, the growing popularity of Korean culture in Poland has become increasingly noticeable. This trend observed is part of a global rise in interest in Korean culture, referred to as the “Korean wave”. Among the factors contributing to the increasing fascination with South Korea is the popularity of Korean television series available via streaming platforms. The aim of this article is to compare the table etiquette principles promoted in Korean dramas with the recommendations found in online guides on this subject available in Polish. Despite the trend toward South Korean culture in Poland, there is still a limited number of studies on its culture and customs. The choice of the topic concerning table manners is not accidental. For Koreans, both the preparation of dishes and the rules of etiquette that dictate how meals should be consumed are of significant importance. For the purpose of this study, information from Polish-language online guides was selected and compared. The research material, in the form of scenes from television series, was drawn from Korean productions available on the Netflix streaming platform. The scenes were selected in a way to enable the analysis of the etiquette in both verbal and non-verbal layers, focusing on the basic rules currently followed at the Korean table in family, social, and professional settings. The results of the analysis can serve both theoretical and practical purposes, providing a comprehensive and synthesized set of essential information that may be useful for individuals traveling to South Korea, fans of Korean cuisine visiting restaurants offering Korean specialties, and employees working in Korean companies in Poland.